2020
DOI: 10.15252/embj.2019103889
|View full text |Cite
|
Sign up to set email alerts
|

Proteasomal degradation induced by DPP9‐mediated processing competes with mitochondrial protein import

Abstract: Plasticity of the proteome is critical to adapt to varying conditions. Control of mitochondrial protein import contributes to this plasticity. Here, we identified a pathway that regulates mitochondrial protein import by regulated N-terminal processing. We demonstrate that dipeptidyl peptidases 8/9 (DPP8/9) mediate the N-terminal processing of adenylate kinase 2 (AK2) en route to mitochondria. We show that AK2 is a substrate of the mitochondrial disulfide relay, thus lacking an N-terminal mitochondrial targetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 94 publications
(141 reference statements)
2
29
0
Order By: Relevance
“…The top ranking TP53 regulation pathway in our analyses indicates that DPP8 and DPP9 overexpression could be oncogenic in human HCC. The downregulation of metabolism genes with DPP8 and DPP9 upregulation concords with previous data showing that DPP9 deficiency dysregulates metabolic pathways in neonatal liver and gut [ 54 ], and that DPP9 hydrolyses metabolism related substrates including adenylate kinase 2 [ 62 , 63 ] and nucleobindin1 [ 64 ] and regulates preadipocyte differentiation [ 65 ]. Moreover, people with obesity are more likely to develop HCC [ 66 , 67 ].…”
Section: Discussionsupporting
confidence: 85%
“…The top ranking TP53 regulation pathway in our analyses indicates that DPP8 and DPP9 overexpression could be oncogenic in human HCC. The downregulation of metabolism genes with DPP8 and DPP9 upregulation concords with previous data showing that DPP9 deficiency dysregulates metabolic pathways in neonatal liver and gut [ 54 ], and that DPP9 hydrolyses metabolism related substrates including adenylate kinase 2 [ 62 , 63 ] and nucleobindin1 [ 64 ] and regulates preadipocyte differentiation [ 65 ]. Moreover, people with obesity are more likely to develop HCC [ 66 , 67 ].…”
Section: Discussionsupporting
confidence: 85%
“…The top ranking TP53 regulation pathway in our analyses indicates that DPP8 and DPP9 overexpression could be oncogenic in human HCC. The downregulation of metabolism genes with DPP8 and DPP9 upregulation concords with previous data showing that DPP9 deficiency dysregulates metabolic pathways in neonatal liver and gut [53], and that DPP9 hydrolyses metabolism related substrates including adenylate kinase 2 [59,60] and nucleobindin1 [61] and regulates preadipocyte differentiation [62]. Moreover, people with obesity are more likely to develop HCC [63,64].…”
Section: Discussionsupporting
confidence: 84%
“…Several anti-MLS genes in the SHAP analysis were also selected in the linear models, including C6orf89 and DPP9 ( Supplementary Table S6 ). With regards to their functions, it has been shown that C6orf89 exhibits histone deacetylase (HDAC) enhancer properties [ 59 ], while DPP9 regulates mitochondrial protein levels and localization [ 60 ], and is linked to a variety of age-related pathologies including type 2 diabetes, obesity and cancer.…”
Section: Resultsmentioning
confidence: 99%